2020
DOI: 10.3389/fcimb.2020.581986
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genes Involved in Escherichia coli Persistence to Tosufloxacin

Abstract: Persisters are metabolically quiescent phenotypic variants of the wild type that are tolerant to cidal antibiotics, and the mechanisms of persister formation and survival are complex and not completely understood. To identify genes involved in persistence to tosufloxacin, which has higher activity against persisters than most other quinolones, we screened the E. coli KEIO mutant library using a different condition from most persister mutant screens (6 h) with a longer exposure of 18 h with tosufloxacin. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This observation demonstrated that the commonly upregulated genes follow consistency with different types of antibiotics; Amp targets cell wall formation 21 , while Cip targets DNA synthesis 41 .Our goal was to determine how these genes were related to persister survival. We build off what we knew from previous persister and transcriptomic analysis studies 24,[42][43][44][45][46][47][48] . Previous studies identified several persister-related genes including oxyR, dnaK, sucB, relA, rpoS, clpB, mqsR, and recA, which were found to be related to prominent persister formation with multiple antibiotics treatment 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation demonstrated that the commonly upregulated genes follow consistency with different types of antibiotics; Amp targets cell wall formation 21 , while Cip targets DNA synthesis 41 .Our goal was to determine how these genes were related to persister survival. We build off what we knew from previous persister and transcriptomic analysis studies 24,[42][43][44][45][46][47][48] . Previous studies identified several persister-related genes including oxyR, dnaK, sucB, relA, rpoS, clpB, mqsR, and recA, which were found to be related to prominent persister formation with multiple antibiotics treatment 42 .…”
Section: Resultsmentioning
confidence: 99%
“…1. The fact that persister-related genes are constantly identified, and if one mechanism is reasoned for persister formation by one research group, another's group disclaimed that mechanism [42][43][44][45][46]71 . This suggests not one gene is responsible for persister formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in tatC and edd genes were identified at timepoint 7 in lineage 1. Mutations in tatC and other genes, gltI, hlpA , ruvC , ddlB and ydfI, were found to result in tolerance to tosufloxacin in E. coli [ 27 ]. TatC, the primary substrate receptor, is part of the twin-arginine translocation (Tat) system needed to transport folded proteins across biological membranes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other quinolones, tosufloxacin had higher activity against E. coli tolerant persister cells [ 25 ]. In our previous work to identify genes involved in E. coli persistence, we found that mutation in the gltI encoding glutamate/aspartate transport protein showed increased susceptibility to tosufloxacin [ 26 ], suggesting that glutamate transporters may be involved in bacterial tolerance. In this study, to evaluate the role of glutamate transporter GltS, as well as two other glutamate transporters, GltP and GltI, in E. coli tolerance and pathogenicity, we constructed their deletion mutants in both E. coli K12 strain BW25113 and uropathogenic E. coli UTI89, followed by analysis of their tolerance to various antibiotics and stressors in vitro and their pathogenicity in human bladder epithelial cells and mouse urinary tract infections.…”
Section: Introductionmentioning
confidence: 99%